Analyzing the Role of User-Generated Content in the Growth of Online Video Platforms - Christian, Yefta; Wijaya, Vincent (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2023)
The growth of online video platforms in recent years has been driven by a multitude of factors, including advancements in technology and the increasing availability of high-speed internet. However, one of the most significant factors contributing to the success of these platforms is the role of user-generated content (UGC). UGC refers to content created and shared by users of online video platforms, rather than by the platforms themselves. This thesis aims to analyze the role of UGC in the growth of online video platforms by exploring the ways in which UGC contributes to platform success. By examining the impact of UGC, this research provides insights into the evolving landscape of online video and the ways in which UGC shapes it. The study of UGC and its role in the growth of online video platforms has significant implications for marketers, content creators, and platform owners. By understanding the impact of UGC, stakeholders can develop more effective strategies for creating and distributing content on these platforms. This research contributes to the academic understanding of the evolving landscape of online video and the role of UGC in shaping it. Overall, this thesis provides valuable insights into the ways in which UGC drives the growth of online video platforms and highlights its importance for the future of online video.